Communication Systems - Stern, Harold P.E.; Mahmoud, Samy A ([S.l.] : Prentice Hall, 2003)
Using three parallel teaching approaches$1 (Brigorous mathematical, graphical, and intuitive, this book offers various types of learners a practical and deep understanding of communication systems. Emphasis on the theme of cost vs. performance tradeoffs throughout the book provides a framework and motivation for all the topics examined in it. Fundamentals of frequency domain analysis are reinforced through graphical techniques and communications-oriented examples. Chapter topics cover digital baseband modulation techniques, baseband receiver design, digital bandpass modulation and demodulation techniques, multiplexing techniques, analog-to-digital conversion, basics of information theory and data compression, and basics of error control coding. For electrical engineers interested in the field of communication systems and digital communicationss
Keywords: Telecommunication systems; Design and construction; Telecommunication systems; Design